Tranexamic acid versus placebo to reduce perioperative blood transfusion in patients undergoing liver resection: protocol for the haemorrhage during liver resection tranexamic acid (HeLiX) randomised controlled trial. Issue 2 (24th February 2022) - Karanicolas, Paul Jack; Lin, Yulia; McCluskey, Stuart; Roke, Rachel; Tarshis, Jordan; Thorpe, Kevin E; Ball, Chad G; Chaudhury, Prosanto; Cleary, Sean P; Dixon, Elijah; Eeson, Gareth; Moulton, Carol-Anne; et al.
Abstract : Introduction: Despite use of operative and non-operative interventions to reduce blood loss during liver resection, 20%–40% of patients receive a perioperative blood transfusion. Extensive intraoperative blood loss is a major risk factor for postoperative morbidity and mortality and receipt of blood transfusion is associated with serious risks including an association with long-term cancer recurrence and overall survival. In addition, blood products are scarce and associated with appreciable expense; decreasing blood transfusion requirements would therefore have health system benefits. Tranexamic acid (TXA), an antifibrinolytic, has been shown to reduce the probability of receiving a blood transfusion by one-third for patients undergoing cardiac or orthopaedic surgery. However, its applicability in liver resection has not been widely researched. Methods and analysis: This protocol describes a prospective, blinded, randomised controlled trial being conducted at 10 sites in Canada and 1 in the USA. 1230 eligible and consenting participants will be randomised to one of two parallel groups: experimental (2 g of intravenous TXA) or placebo (saline) administered intraoperatively. The primary endpoint is receipt of blood transfusion within 7 days of surgery. Secondary outcomes include blood loss, postoperative complications, quality of life and 5-year disease-free and overall survival. Ethics and dissemination: This trial has been approved by the research ethics boards at participating centres and Health Canada (parent control number 177992) and is currently enrolling participants. All participants will provide written informed consent. Results will be distributed widely through local and international meetings, presentation, publication and ClinicalTrials.gov. Trial registration number: NCT02261415 .